FRAUD ANALYSIS USING THE BENEISH RATIO INDEX METHOD IN MINING SUB-SECTOR COMPANIES LISTED ON THE IDX IN 2020 – 2025 - Dede Pramurza (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study aims to detect indications of financial statement fraud in mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2025 period using the Beneish Ratio Index (Beneish M-Score). This study employs a descriptive quantitative approach utilizing secondary data in the form of the companies' annual financial reports. The analysis is conducted by calculating eight Beneish ratios: the Days Sales in Receivables Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), Depreciation Index (DEPI), Sales General and Administrative Expenses Index (SGAI), Leverage Index (LVGI), and Total Accruals to Total Assets (TATA), to classify companies into non-manipulators, gray companies, and manipulators. The results indicate that not all mining sub-sector companies fell into the non-manipulators category during the observation period. Several companies were identified as manipulators or gray companies in certain years, indicating the potential for less than fair presentation of financial statements. The DSRI, GMI, AQI, and SGI ratios were the most sensitive indicators in detecting potential manipulation. These findings confirm that the Beneish M-Score method is effective as an early warning system, but cannot be used as definitive evidence of fraud. This research is expected to contribute to the development of accounting literature and provide consideration for auditors, regulators, and investors in improving the quality of transparency and accountability of financial reporting in the mining sector.